2023
DOI: 10.1186/s12958-023-01068-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vitamin D supplementation on reproductive outcomes of infertile patients: a systematic review and meta-analysis

Abstract: Background Low vitamin D status has been associated with an increased risk for infertility. Recent evidence regarding the efficacy of vitamin D supplementation in improving reproductive outcomes is inconsistent. Therefore, this systematic review was conducted to investigate whether vitamin D supplementation could improve the reproductive outcomes of infertile patients and evaluate how the parameters of vitamin D supplementation affected the clinical pregnancy rate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…However, some studies did not find this association ( Subramanian et al , 2022 ). Moreover, clinical evidence from various RCTs indicated that vitamin D supplementation did not improve miscarriage rates as expected ( Tamblyn et al , 2022 ; Zhou et al , 2022 ; Meng et al , 2023 ). Although abundant exposure to ultraviolet radiation during the summer leads to a significant increase in serum vitamin D levels, research has not found any evidence suggesting improved clinical pregnancy rates, live birth rates, or reduced miscarriage rates in women undergoing oocyte retrieval and embryo transfer during the summer ( Carlsson Humla et al , 2022 ).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…However, some studies did not find this association ( Subramanian et al , 2022 ). Moreover, clinical evidence from various RCTs indicated that vitamin D supplementation did not improve miscarriage rates as expected ( Tamblyn et al , 2022 ; Zhou et al , 2022 ; Meng et al , 2023 ). Although abundant exposure to ultraviolet radiation during the summer leads to a significant increase in serum vitamin D levels, research has not found any evidence suggesting improved clinical pregnancy rates, live birth rates, or reduced miscarriage rates in women undergoing oocyte retrieval and embryo transfer during the summer ( Carlsson Humla et al , 2022 ).…”
Section: Discussionmentioning
confidence: 65%
“…Although the results of this article and current clinical research did not support the prevention of miscarriage through vitamin D supplementation before and during pregnancy ( Tamblyn et al , 2022 ; Zhou et al , 2022 ; Meng et al , 2023 ), we still advocate for the supplementation of vitamin D in women preparing for pregnancy and in pregnant women with vitamin D insufficiency or deficiency in achieving normal levels of serum 25OHD. Pregnant women have an increased demand for vitamin D during pregnancy.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Although the European Society of Human Reproduction and Embryology (ESHRE) guideline for RIF does not recommend vitamin D testing and replacement given the lack of established evidence, 3 a recent systematic review and meta‐analysis demonstrated that clinical pregnancy rates in IVF treatment were increased by 2.06‐fold after vitamin D replacement in women with 25OHVD levels <30 ng/mL (95% CI: 1.32–3.22). 75 Among such women, those who received daily supplementation for >30 days had significantly better clinical pregnancy rates, compared to weekly or longer intervals and/or <30 days. In our previous report, vitamin D replacement at 25 μg/day for 3 months in patients with 25OHVD levels <30 ng/mL promoted sufficient levels in only half of them.…”
Section: Tests and Treatments For Implantation Failurementioning
confidence: 99%
“…VDR null mice have also shown uterine hypoplasia and are responsive to estrogen priming, indicating the role of hypogonadism in uterine defects [ 91 ]. Based on a meta-analysis, a moderate daily intake of vitamin D supplements may enhance the chances of clinical pregnancy in infertile women and can have a positive impact on pregnancy outcomes [ 92 ].…”
Section: Reproductive Disorders Associated With a Lack Of Vitamin Dmentioning
confidence: 99%